Glycan biomarkers of autoimmunity and bile acid-associated alterations of the human glycome Primary biliary cirrhosis and primary sclerosing cholangitis-specific glycans - Maverakis, Emanual (Clinical immunology (Orlando, Fla.), 2021)
Copyright © 2021 The Author(s). Published by Elsevier Inc. All rights reserved.